2003
DOI: 10.1038/sj.leu.2402946
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokines and their role in the development of major transplant-related complications in the early phase after allogeneic bone marrow transplantation

Abstract: Serum levels of interleukin-6 (IL-6), interleukin-8 (IL-8) and tumor necrosis factor (TNF)-alpha were frequently measured during the first 30 days after allogeneic bone marrow transplantation (BMT) in 84 consecutive adult patients. Major transplant-related complications (MTCs) occurred in 33% of cases and included veno-occlusive liver disease, idiopathic pneumonia syndrome, severe endothelial leakage syndrome and 4grade II acute graft-versus-host disease. Compared with patients having minor complications, thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(103 citation statements)
references
References 40 publications
7
91
0
5
Order By: Relevance
“…As significant inflammation was thought to be a major part of the initial trigger of acute GVHD, early studies focused on acute-phase reactants, such as IL-1 and IL-6, in addition to TNF-a. [11][12][13][14] A Japanese study measured C-reactive protein in a heterogeneous group of over 200 patients with analysis showing that although higher C-reactive protein levels could predict for acute GVHD, other factors including conditioning regimen intensity, infection and unrelated donors were also associated with higher levels. 15 Acute GVHD has traditionally thought to be a Th1 response, and thus, cytokines including IL-12 and IFN-g have been shown to have correlations with acute GVHD.…”
Section: Il-2mentioning
confidence: 99%
“…As significant inflammation was thought to be a major part of the initial trigger of acute GVHD, early studies focused on acute-phase reactants, such as IL-1 and IL-6, in addition to TNF-a. [11][12][13][14] A Japanese study measured C-reactive protein in a heterogeneous group of over 200 patients with analysis showing that although higher C-reactive protein levels could predict for acute GVHD, other factors including conditioning regimen intensity, infection and unrelated donors were also associated with higher levels. 15 Acute GVHD has traditionally thought to be a Th1 response, and thus, cytokines including IL-12 and IFN-g have been shown to have correlations with acute GVHD.…”
Section: Il-2mentioning
confidence: 99%
“…7,18 Moreover, hepatic endothelial damage is associated with conditions, such as sepsis, impaired liver function, veno-occlusive disease, and graft versus host disease, that could potentially benefit from endothelial reconstitution. [22][23][24][25] In principle, transplanted LSEC could enter the liver through the systemic or portal circulation, because hepatic sinusoids receive blood from both the portal vein (70%) and the hepatic artery (30%). 26 However, if LSEC escaped from the liver by exiting through central veins as a result of their small size, engraftment of LSEC could be affected.…”
Section: E Ndothelial Cells (Ec) Play Critical Roles In Orga-mentioning
confidence: 99%
“…Elevated levels of pro-inflammatory cytokines associated with activated macrophages such as TNF-a and macrophage inflammatory protein-1a might have contributed to the development of graft failure and exacerbation of endothelial complications, resulting in higher NRM rates in the HP group. 6,7,10,26,27 That C-reactive protein values were found to be higher in the HP group than in the non-HP group suggested that early macrophage activation was associated with a hyperinflammatory state. Future studies to measure the serum cytokine levels are warranted.…”
Section: Tablementioning
confidence: 95%
“…3 In addition to aGVHD, pro-inflammatory cytokine release is implicated in the pathogenesis of various early complications after allo-HSCT, such as sinusoidal obstruction syndrome, engraftment syndrome (ES) and capillary leakage syndrome. [4][5][6][7] Although the role of macrophages in these complications is undetermined, macrophages have an ability to secrete significant amounts of pro-inflammatory cytokines. 2 Furthermore, fatal outcomes of hemophagocytic syndrome after allo-HSCT have been described in case reports.…”
Section: Introductionmentioning
confidence: 99%